Implementasi Jaringan Cloud dan Server Open Data Analytic Room di Diskominfo Kabupaten Bengkayang - Azriel Christian Nurcahyo; Hartono Pranjoto (Journal of Information Technology, 2025)
This study focuses on the implementation of a cloud network and Open Data Analytic Room server at the Bengkayang District Communication and Informatics Office (Diskominfo), which aims to enhance electronic governance by utilizing cloud technology, virtualization, and integrated analytics systems. The infrastructure is built around a scalable, modular cloud network designed for optimal data distribution and real-time analytics, using virtual machines hosted on Ubuntu 24.04 LTS with KVM (Kernel-based Virtual Machine) virtualization. Security measures such as CPGuard, LiteSpeed, and Softaculous have been integrated to ensure data protection and efficient management. The performance of the system was evaluated through Quality of Service (QoS) testing using tools like Mikrotik RouterOS and Wireshark. The results show excellent performance, with a throughput of 89.5 Mbps, packet loss of 0.23%, jitter of 2.1 ms, and latency of 12.8 ms. These outcomes confirm the system’s efficiency in handling large data traffic, supporting real-time analytics, and enhancing decision-making processes in governance. The study concludes that the cloud-based data analytic room infrastructure at Diskominfo Bengkayang provides a reliable foundation for future data governance systems, ensuring transparency, security, and flexibility for the local government’s (Bengkayang) data management needs.Keywords: Cloud Network, Open Data Analytic Room, Server, Quality of Service, Virtualization, Cloud Infrastructure, Data Governance.